White calcium stone-polyethylene glycol-polylactic acid shape memory polymer, preparation method thereof and application of white calcium stone-polyethylene glycol-polylactic acid shape memory polymer in preparation of bone repair scaffold

By combining white phosphate piezoelectric particles with polylactic acid and polyethylene glycol, a white phosphate-polyethylene glycol-polylactic acid shape memory polymer bone repair stent was prepared, which solved the problem that the existing bone repair stent did not affect bone tissue repair enough under stress, and achieved the low glass transition temperature, good electroactivity and strong shape memory function of the bone repair stent, which was suitable for the internal temperature and bone repair needs of the human body.

CN119875333APending Publication Date: 2025-04-25HEBEI UNIV OF TECH

Patent Information

Application Number
CN202510115443.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing bone repair stents have insufficient impact on bone tissue repair under stress, and commonly used piezoelectric materials such as barium titanate have poor processability and lack of toughness, which limits their application scope.

Method used

Using white phosphite-polyethylene glycol-polylactic acid shape memory polymer, a bone repair scaffold with low glass transition temperature, good electroactive and strong shape memory functions was prepared by compounding white phosphite piezoelectric particles with polylactic acid and polyethylene glycol.

Benefits of technology

The bone repair stent responds sensitively under temperature stimulation, and the glass transition temperature is reduced to 40-50°C. It is more suitable for the internal temperature of the human body and has electroactive properties, which can speed up the bone repair process. It is non-toxic, stable in chemical properties, and has good biocompatibility and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875333A_ABST
    Figure CN119875333A_ABST
Patent Text Reader

Abstract

The invention provides a whitmanite-polyethylene glycol-polylactic acid shape memory polymer, a preparation method thereof and an application of the whitmanite-polyethylene glycol-polylactic acid shape memory polymer in preparation of a bone repair scaffold, and belongs to the technical field of biomedical materials. According to the invention, polyethylene glycol and white phosphorus calcium stone are respectively used as modified materials for constructing an electrophysiological microenvironment to promote osteogenesis and adjust the deformation temperature of a polymer, and are physically blended with a polylactic acid matrix to prepare the 3D printing shape memory polylactic acid-based composite material. According to the stress condition of the human thighbone, the stress induction structure bone scaffold is designed and accords with the biological force line distribution and staggered structure characteristics of the human thighbone. The stress-induced structure bone repair scaffold is prepared through the 3D printing technology, the performance and glass transition temperature of the scaffold are low, the electroactivity is good, the shape memory function is strong, the biocompatibility and the degradability are good, and a new choice is provided for the bone repair scaffold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a whiojasite-polyethylene glycol-polylactic acid shape memory polymer and a preparation method thereof, and application thereof in preparing a bone repair scaffold. Background Art

[0002] With the increasing aging of the population and the frequent traffic accidents in recent years, bone defects caused by bone tumors, degenerative diseases, trauma and infection are greatly affecting people's quality of life. The demand for orthopedic implants is increasing day by day. Customizable porous bone repair scaffolds are the subject of extensive research in current bone repair and replacement research. The ideal bone repair scaffold should meet its structural and functional requirements. At present, the common structures of bone repair scaffolds are grid structures and three-periodic minimal surface structures (TPMS). Jiamusi University 3D printed a bionic mandibular scaffold (CN113768666B) based on TPMS design, which only considered the contour design and the matching of the scaffold with the overall performance of the autologous bone, and did not fully consider the influence of its stress condition on bone tissue repair. Its bionic function has not been fully realized, and its bone tissue repair ability needs to be improved.

[0003] In terms of bone repair scaffold function, electrical stimulation (ES) has been shown to be a beneficial treatment for bone defects, which can significantly improve fracture healing rates and enhance the effectiveness of bone transplantation therapy. Piezoelectric materials, due to their piezoelectric properties, can generate microcurrents in response to self-generated movement or external stimulation. Piezoelectric materials can be used at the site of bone defects to regulate the physiological electrical microenvironment, thereby promoting bone regeneration. Common piezoelectric materials such as barium titanate (BT) are widely used in bone repair scaffolds. The Dalian Institute of Chemical Physics, Chinese Academy of Sciences, doped BT into polyaryletherketone to prepare a piezoelectric bone repair scaffold (CN118949128A), and Beijing Institute of Technology mixed BT and calcium phosphate for 3D printing to prepare a piezoelectric hard bone scaffold. However, the poor processability and lack of toughness of BT limit its scope of use.

[0004] Shape memory polymers (SMP) have attracted much attention in the field of bone regeneration due to their biocompatibility, processability and excellent shape recovery performance. When used for repairing irregular or minor bone defects, SMP scaffolds allow closer contact with adjacent bone tissue to achieve bone integration and can be implanted through minimally invasive surgery, causing little harm to patients. Polylactic acid (PLA) is a shape memory polymer material commonly used in biomedicine. It has excellent mechanical properties, high shape memory function, and superior biocompatibility and degradability. However, since the glass transition temperature of the PLA material itself is between 55 and 70°C, temperature-responsive shape memory recovery in the human body will cause discomfort to the human body. Therefore, polyethylene glycol (PEG) is added to lower the glass transition temperature to match the human body temperature. Combining piezoelectric ceramics with shape memory polymers, in which the ceramic phase can convert electrical energy and mechanical energy, and the polymer matrix can transmit stress, can improve some limitations such as poor processing performance and insufficient toughness. Summary of the invention

[0005] The purpose of the present invention is to provide a white patite-polyethylene glycol-polylactic acid shape memory polymer and a preparation method thereof and an application in the preparation of a bone repair scaffold. The prepared shape memory polymer bone repair scaffold has a low glass transition temperature, good electrical activity, strong shape memory function, good biocompatibility and degradability, and a structure that conforms to the biological force line distribution and staggered structural characteristics of the human femur.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a whitlockite-polyethylene glycol-polylactic acid shape memory polymer, comprising the following steps:

[0008] Calcium hydroxide, magnesium hydroxide, water and phosphoric acid are mixed, heated for reaction, aged and dried to obtain white phosphate calcium stone;

[0009] annealing the whiojasite to obtain whiojasite piezoelectric particles;

[0010] Compounding polylactic acid, polyethylene glycol, a dissolving agent and white patrolite piezoelectric particles, and drying to obtain a white patrolite-polyethylene glycol-polylactic acid composite material;

[0011] Extruding the calcium phosphate-polyethylene glycol-polylactic acid composite material to obtain a shape memory polymer composite wire;

[0012] The shape memory polymer composite filament is 3D printed to obtain the white phosphate-polyethylene glycol-polylactic acid shape memory polymer.

[0013] Preferably, the molar ratio of calcium hydroxide, magnesium hydroxide and phosphoric acid is 0.37-0.38:0.12-0.13:0.4-0.6.

[0014] Preferably, the temperature of the heating reaction is 90-100° C., and the time is 8-12 hours; the temperature of the aging is room temperature, and the time is 10-16 hours.

[0015] Preferably, the annealing treatment is performed at a temperature of 600 to 750° C. and for a time of 2 to 4 hours.

[0016] Preferably, the content of the white patite piezoelectric particles in the white patite-polyethylene glycol-polylactic acid composite material is 10 to 30 wt%; the content of the polyethylene glycol in the white patite-polyethylene glycol-polylactic acid composite material is 3 to 15 wt%; the content of the polylactic acid in the white patite-polyethylene glycol-polylactic acid composite material is 60 to 86 wt%.

[0017] Preferably, the solvent includes dichloromethane, chloroform or ethyl acetate; the ratio of the mass of the solvent to the total mass of polyethylene glycol and polylactic acid is 1:4 to 1:7.

[0018] Preferably, the 3D printing conditions include: a printing temperature of 190 to 230° C., a printing speed of 50 to 100 mm / s, and a printing layer thickness of 0.1 to 0.3 mm.

[0019] Preferably, the temperatures of the two extrusion stages are 150-185°C and 140-170°C.

[0020] The present invention provides a white patrickite-polyethylene glycol-polylactic acid shape memory polymer prepared by the preparation method described in the above technical scheme.

[0021] The present invention provides an application of the white patrolite-polyethylene glycol-polylactic acid shape memory polymer described in the above technical solution in the preparation of a bone repair scaffold, and the application method comprises:

[0022] Using NX modeling software, modeling was performed based on the biological force line distribution and staggered structural characteristics of the human femur to obtain a stress-induced structural bone scaffold model;

[0023] After exporting the stress-induced structural bone scaffold model to an STL file, slicing is performed using slicing software to generate a fused deposition model 3D printing G code, and the shape memory polymer composite wire material described in the above technical solution is 3D printed to obtain a bionic structure shape memory polymer bone repair scaffold;

[0024] The modeling curve of the stress-induced structural bone scaffold is y 3 =10x 2, the spacing is 0.4~0.8mm, and the curve diameter is 0.4~0.8mm.

[0025] The present invention provides a method for preparing a white apatite-polyethylene glycol-polylactic acid shape memory polymer. The present invention adopts polyethylene glycol and white apatite as modified materials for constructing an electrophysiological microenvironment to promote osteogenesis and regulating the deformation temperature of a polymer, respectively, and physically blends them with a polylactic acid matrix to prepare a 3D printed shape memory polylactic acid-based composite material, and combines the fused deposition 3D printing technology with the 3D printing technology to prepare a 3D printed shape memory polylactic acid-based bone repair scaffold. The present invention models the bone scaffold model based on the biological force line distribution and staggered structural characteristics in the human femur, models the stress-induced structural bone scaffold model, bionic design and 3D print a porous orthopedic implant with a stress-induced structure that can accurately control the stress-strain orientation, and obtains a white phosphate-polyethylene glycol-polylactic acid bionic structure shape memory polymer bone repair scaffold, which has the performance of low glass transition temperature, good electrical activity, strong shape memory function, good biocompatibility and degradability, and a stress-induced structure that conforms to the biological force line distribution and staggered structural characteristics in the human femur, providing a new choice for bone repair scaffolds and expanding the application scope of polylactic acid-based composite materials in the fields of biomedicine and the like.

[0026] The invention designs a stress induction structure according to the biological force line distribution characteristics of human femur, and the adjustable range of the spacing and curve is 0.4-0.8mm, and the porosity range is 30-70%.

[0027] The invention can change the content of white phosphate (10-30%) according to different actual needs, thereby changing the electrical activity and shape memory performance of the composite material, and its CV curve has significantly different current changes and increases, and the shape recovery rate is 94-99%.

[0028] The present invention can change the PEG content (3-15%) according to different actual needs, thereby changing the shape memory performance and glass transition temperature of the composite material, so that its shape memory can meet different requirements for the performance of the composite material under different biomedical conditions. The glass transition temperature is 40-55°C and the shape recovery rate is 98-99.5%.

[0029] The white calcium phosphate-polyethylene glycol-polylactic acid bionic structure shape memory polymer bone repair scaffold prepared by the present invention is sensitive to temperature stimulation; at the same time, its glass transition temperature is between 40 and 50°C, which is 10 to 20°C lower than that of polylactic acid material, and is more suitable for the temperature requirements of the human body. It also has electrical activity and can accelerate the bone repair process.

[0030] The bionic structure shape memory polymer bone repair scaffold prepared by the invention is non-toxic and harmless, has stable chemical properties, good compatibility with human tissues, and has excellent in vivo and in vitro degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Model diagram and physical diagram of stress-induced structural bone scaffolds established in Examples 1 to 3 of the present invention, (a) stress-induced model diagram of different spacings and diameters in Examples 1 to 3; (b) physical diagram of stress-induced structural bone scaffolds prepared in Examples 1 to 3;

[0032] Figure 2 The XRD pattern of the white calcium phosphate prepared in Example 1 of the present invention;

[0033] Figure 3 DSC curves of shape memory polymer bone repair scaffolds with different contents of white patrickite piezoelectric particles and different contents of polyethylene glycol prepared in Examples 1 to 3 of the present invention and Comparative Examples 2 to 3;

[0034] Figure 4 Shape recovery rates of different white calcium phosphate piezoelectric particles and shape memory polymer bone repair scaffolds with different polyethylene glycol contents prepared in Examples 1 to 3 and Comparative Examples 1 to 4;

[0035] Figure 5 CV curves of the electroactivity of the shape memory polymer bone repair scaffolds with different white calcium phosphate piezoelectric particles and polyethylene glycol contents prepared in Examples 1 to 2 and Comparative Examples 1 and 4. DETAILED DESCRIPTION

[0036] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0037] The present invention provides a method for preparing a whitlockite-polyethylene glycol-polylactic acid shape memory polymer, comprising the following steps:

[0038] Calcium hydroxide, magnesium hydroxide, water and phosphoric acid are mixed, heated for reaction, aged and dried to obtain white phosphate calcium stone;

[0039] annealing the whiojasite to obtain whiojasite piezoelectric particles;

[0040] Compounding polylactic acid, polyethylene glycol, a dissolving agent and white patrolite piezoelectric particles, and drying to obtain a white patrolite-polyethylene glycol-polylactic acid composite material;

[0041] Extruding the calcium phosphate-polyethylene glycol-polylactic acid composite material to obtain a shape memory polymer composite wire;

[0042] The shape memory polymer composite filament is 3D printed to obtain the white phosphate-polyethylene glycol-polylactic acid shape memory polymer.

[0043] The invention comprises mixing calcium hydroxide, magnesium hydroxide, water and phosphoric acid, heating and reacting the mixture, aging the mixture and drying the mixture to obtain white phosphate calcium carbonate.

[0044] In the present invention, the molar ratio of calcium hydroxide, magnesium hydroxide and phosphoric acid is preferably 0.37-0.38:0.12-0.13:0.4-0.6, and more preferably 0.37:0.13:0.5.

[0045] In the present invention, the phosphoric acid is preferably used in the form of a phosphoric acid solution, and the concentration of the phosphoric acid solution is preferably 0.4 to 0.6 mol / L, more preferably 0.5 mol / L.

[0046] The present invention has no particular limitation on the amount of water used, and the amount of water used can be adjusted according to actual needs to ensure that the materials are evenly dispersed.

[0047] The present invention preferably adds calcium hydroxide and magnesium hydroxide into deionized water, stirs at 90-100° C. for 0.5-1h, then drops phosphoric acid to react, ages after the reaction, washes by centrifugation until neutral, and dries in a blast drying oven to obtain white phosphate calcium carbonate.

[0048] In the present invention, the temperature of the heating reaction is preferably 90-100°C, more preferably 100°C, and the time is preferably 8-12h, more preferably 10h; the temperature of the aging is preferably room temperature, and the time is preferably 10-16h, more preferably 14h; the temperature of the drying is preferably 80-100°C, more preferably 80-90°C, and the time is preferably 24-36h, more preferably 36h.

[0049] White phosphate (WH) is a natural magnesium-containing inorganic particle that can release Mg during the slow degradation process. 2+ , Ca 2+ and PO4 3- Plasma can promote the formation of new bones. At the same time, due to its non-centrosymmetric structure, it has piezoelectric properties after annealing and polarization, and can be used as piezoelectric materials for bone repair.

[0050] After obtaining the white phosphate, the present invention performs annealing treatment on the white phosphate to obtain white phosphate piezoelectric particles.

[0051] In the present invention, the annealing temperature is preferably 600-750°C, more preferably 650-680°C, and the time is preferably 2-4 hours, more preferably 2.5-3 hours. In the present invention, the whitlockite ceramic particles have piezoelectric properties through annealing.

[0052] After obtaining the white patite piezoelectric particles, the present invention compounds polylactic acid (PLA), polyethylene glycol (PEG), a dissolving agent and the white patite piezoelectric particles, and then dries to obtain the white patite-polyethylene glycol-polylactic acid composite material.

[0053] The present invention has no special limitation on the sources and specific specifications of the polylactic acid and polyethylene glycol, and any commercially available products known in the art may be used; in the embodiments of the present invention, the polylactic acid pellets (4032D) are from Natureworks, USA; and polyethylene glycol 1500 is from Sinopharm Chemical Reagent Co., Ltd.

[0054] In the present invention, the content of the white patite piezoelectric particles in the white patite-polyethylene glycol-polylactic acid composite material is preferably 10-30wt%, more preferably 20wt%; the content of the polyethylene glycol in the white patite-polyethylene glycol-polylactic acid composite material is preferably 3-15wt%, more preferably 4-8wt%; the content of the polylactic acid in the white patite-polyethylene glycol-polylactic acid composite material is preferably 60-86wt%, more preferably 65-82wt%, and further preferably 72-76wt%.

[0055] In the present invention, the solvent preferably includes dichloromethane, chloroform or ethyl acetate; the ratio of the mass of the solvent to the total mass of polyethylene glycol and polylactic acid is preferably 1:4 to 1:7, more preferably 1:5 to 1:6.

[0056] The present invention preferably dries white patite piezoelectric particles (PWH), PEG and PLA in a blast drying oven respectively, mixes the dried PLA and PEG with a solvent, stirs them at room temperature for 5 to 8 hours (more preferably 6 to 7 hours) using a magnetic stirrer until they are uniform and stable, then adds piezoelectric ceramic particles, continues ultrasonic stirring for 1 hour under a heating state of 40 to 50° C., and then dries in a blast drying oven until the solvent is completely removed to obtain a white patite-polyethylene glycol-polylactic acid composite material, and then pelletizes the mixture for subsequent extrusion.

[0057] In the present invention, the drying temperature is preferably 50-70°C, more preferably 55-60°C, and the drying time is preferably 3 days. In the present invention, the dissolving agent is completely removed by drying to obtain the whiojasite-polyethylene glycol-polylactic acid composite material.

[0058] The present invention has no particular limitation on the pelletizing, and the pelletizing may be performed according to a process well known in the art.

[0059] After obtaining the white patrolite-polyethylene glycol-polylactic acid composite material, the present invention extrude the white patrolite-polyethylene glycol-polylactic acid composite material to obtain a shape memory polymer composite wire material.

[0060] The present invention preferably first uses ABS particles to extrude the single screw extruder, washes the residual material of the extruder, waits for the extrusion part, and then loads the white calcium phosphate-polyethylene glycol-polylactic acid composite material into the single screw extruder hopper, sets the extrusion temperature, and starts to extrude the wire; the wire is extruded through the die mouth, pulled with tweezers, and successively passes through air cooling, a tractor and a wire winding machine, and the diameter of the wire is controlled by controlling the extrusion rate of the extruder and the traction rate of the tractor. The present invention has no special limitation on the diameter of the wire, and it can be adjusted according to actual needs. In an embodiment of the present invention, it is specifically 1.75mm.

[0061] In the present invention, the temperatures of the two stages of extrusion are preferably 150-185°C and 140-170°C, more preferably 180°C and 165°C.

[0062] After obtaining the shape memory polymer composite wire, the present invention performs 3D printing on the shape memory polymer composite wire to obtain the whiolapite-polyethylene glycol-polylactic acid shape memory polymer.

[0063] The 3D printing described in the present invention preferably adopts a fused deposition modeling (FDM) process.

[0064] In the present invention, the 3D printing conditions preferably include: a printing temperature of 190 to 230° C., more preferably 200 to 220° C., a printing speed of 50 to 100 mm / s, more preferably 60 to 80 mm / s, and a printing layer thickness of 0.1 to 0.3 mm, more preferably 0.2 mm.

[0065] The present invention provides a white patrickite-polyethylene glycol-polylactic acid shape memory polymer prepared by the preparation method described in the above technical scheme.

[0066] The present invention provides the use of the white patrickite-polyethylene glycol-polylactic acid shape memory polymer described in the above technical solution in the preparation of a bone repair scaffold.

[0067] In the present invention, the application method preferably includes:

[0068] Using NX modeling software, modeling was performed based on the biological force line distribution and staggered structural characteristics of the human femur to obtain a stress-induced structural bone scaffold model; the density and porosity were changed by changing the spacing and diameter parameters in the bone repair scaffold model;

[0069] After the stress-induced structural bone scaffold model is exported as an STL file, it is sliced ​​using slicing software to generate a fused deposition model 3D printing G code, and the shape memory polymer composite filament described in the above technical solution is placed in a 3D printer for 3D printing to obtain a bionic structure shape memory polymer bone repair scaffold.

[0070] The present invention is specifically based on the characteristics of the interlaced structure formed by the regular intersection of curved lines in the human femur and the distribution characteristics of the biological force lines for modeling.

[0071] The 3D printing parameters for preparing the bionic structure shape memory polymer bone repair scaffold of the present invention are in the same range as the 3D printing parameters of the above-mentioned calcium phosphate-polyethylene glycol-polylactic acid shape memory polymer.

[0072] In the present invention, the modeling curve of the stress-induced structural bone scaffold is y 3 =10x 2 The spacing is 0.4 to 0.8 mm, more preferably 0.6 mm, and the curve diameter is 0.4 to 0.8 mm, more preferably 0.6 mm.

[0073] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0074] In the following examples, dichloromethane, purity 99%, Tianjin Aopusheng Chemical Co., Ltd.;

[0075] Polylactic acid pellets (4032D), Natureworks, USA; polyethylene glycol 1500, Sinopharm Chemical Reagent Co., Ltd.

[0076] Example 1

[0077] 0.074 mol of calcium hydroxide and 0.026 mol of magnesium hydroxide were added to 200 mL of water, stirred at 100°C for 0.5 h, and then 200 mL of a 0.5 mol / L phosphoric acid solution was added dropwise, reacted at 100°C for 10 h, aged at room temperature for 14 h after the reaction, and then centrifuged and washed until neutral, and dried in a blast drying oven at 80°C for 36 h to obtain white calcium phosphate;

[0078] After annealing the whiojasite at 650° C. for 3 hours, whiojasite piezoelectric particles are obtained;

[0079] Weigh white patite piezoelectric particles, polyethylene glycol and polylactic acid pellets in proportion, in the white patite-polyethylene glycol-polylactic acid composite material, the mass percentage of the white patite piezoelectric particles is 10wt.%, the mass percentage of polyethylene glycol is 8wt.%, and the mass percentage of polylactic acid is 82wt.%, the white patite piezoelectric particles, PEG and PLA are dried in a blast drying oven respectively, and then uniformly mixed according to the total mass of polyethylene glycol and polylactic acid and the mass ratio of dichloromethane is 1:6, and stirred at room temperature for 6h using a magnetic stirrer, after the polymers are completely dissolved and mixed uniformly, piezoelectric ceramic particles are added, ultrasonic stirring is continued for 1h under heating at 50°C, and dried in a blast drying oven at 60°C for 3d until the dichloromethane is completely removed, to obtain a white patite-polyethylene glycol-polylactic acid composite material;

[0080] After pelletizing the calcium apatite-polyethylene glycol-polylactic acid composite material, the obtained composite material pellets are loaded into the hopper of a single screw extruder, and the screw extruder temperature is set to 165° C. and 180° C. to start extruding a wire material, the wire material is extruded through a die mouth, and is pulled with tweezers, and sequentially passes through air cooling, a traction machine, and a wire winding machine, and the diameter of the wire material is controlled to be 1.75 mm by controlling the extrusion rate of the extruder and the pulling rate of the traction machine, thereby obtaining a shape memory polymer composite wire material;

[0081] According to the shape parameters of the required bone repair scaffold, the modeling curve is y using the modeling software NX. 3 =10x 2 , the spacing is 0.6 mm, the curve diameter is 0.4 mm, and the stress-induced structural bone scaffold model is established, such as Figure 1 As shown; after exporting the STL file, it is sliced ​​through the slicing software bambu studio to generate the fused deposition 3D printing G code, and the shape memory polymer composite filament is placed in the 3D printer for 3D printing. The printing temperature is 220°C, the printing speed is 80mm / s, and the printing layer thickness is 0.2mm. A bionic structure shape memory polymer bone repair scaffold is obtained, which is recorded as PWH10.

[0082] Example 2

[0083] The preparation of white calcium phosphate piezoelectric particles is the same as in Example 1;

[0084] Weigh white patite piezoelectric particles, polyethylene glycol and polylactic acid pellets in proportion, in the white patite-polyethylene glycol-polylactic acid composite material, the mass percentage of white patite piezoelectric particles is 20wt.%, the mass percentage of polyethylene glycol is 8wt.%, and the mass percentage of polylactic acid powder is 72wt.%, and the piezoelectric ceramic particles, PEG and PLA are dried in a blast drying oven respectively, and then uniformly mixed according to the total mass of polyethylene glycol and polylactic acid and the mass ratio of dichloromethane to each other in a ratio of 1:6, and stirred at room temperature for 6h using a magnetic stirrer, and after the polymers are completely dissolved and mixed uniformly, piezoelectric ceramic particles are added, and ultrasonic stirring is continued for 1h under heating at 50°C, and dried in a blast drying oven at 60°C for 3d until the dichloromethane is completely removed, to obtain a white patite-polyethylene glycol-polylactic acid composite material;

[0085] After pelletizing the calcium apatite-polyethylene glycol-polylactic acid composite material, the obtained composite material pellets are loaded into the hopper of a single screw extruder, and the screw extruder temperature is set to 165° C. and 180° C. to start extruding a wire material, the wire material is extruded through a die mouth, and is pulled with tweezers, and sequentially passes through air cooling, a traction machine, and a wire winding machine, and the diameter of the wire material is controlled to be 1.75 mm by controlling the extrusion rate of the extruder and the pulling rate of the traction machine, thereby obtaining a shape memory polymer composite wire material;

[0086] According to the shape parameters of the required bone repair scaffold, the modeling curve is y using the modeling software NX. 3 =10x 2 , the spacing is 0.6 mm, the curve diameter is 0.6 mm, and the stress-induced structural bone scaffold model is established, such as Figure 1 As shown; after exporting the STL file, it is sliced ​​through the slicing software bambu studio to generate the fused deposition 3D printing G code, and the shape memory polymer composite filament is placed in the 3D printer for 3D printing. The printing temperature is 220°C, the printing speed is 80mm / s, and the printing layer thickness is 0.2mm to obtain a bionic structure shape memory polymer bone repair scaffold, which is recorded as PWH20.

[0087] Example 3

[0088] The preparation of white calcium phosphate piezoelectric particles is the same as in Example 1;

[0089] Weigh white patite piezoelectric particles, polyethylene glycol and polylactic acid pellets in proportion, in the white patite-polyethylene glycol-polylactic acid composite material, the mass percentage of white patite piezoelectric particles is 20wt.%, the mass percentage of polyethylene glycol is 4wt.%, and the mass percentage of polylactic acid powder is 76wt.%, and the piezoelectric ceramic particles, PEG and PLA are dried in a blast drying oven respectively, and then uniformly mixed according to the total mass of polyethylene glycol and polylactic acid and the mass ratio of dichloromethane to each other in a ratio of 1:6, and stirred at room temperature for 6h using a magnetic stirrer, and after the polymers are completely dissolved and mixed uniformly, piezoelectric ceramic particles are added, and ultrasonic stirring is continued for 1h under heating at 50°C, and dried in a blast drying oven at 60°C for 3d until the dichloromethane is completely removed, to obtain a white patite-polyethylene glycol-polylactic acid composite material;

[0090] After pelletizing the calcium apatite-polyethylene glycol-polylactic acid composite material, the obtained composite material pellets are loaded into the hopper of a single screw extruder, and the screw extruder temperature is set to 165° C. and 180° C. to start extruding a wire material, the wire material is extruded through a die mouth, and is pulled with tweezers, and sequentially passes through air cooling, a traction machine, and a wire winding machine, and the diameter of the wire material is controlled to be 1.75 mm by controlling the extrusion rate of the extruder and the pulling rate of the traction machine, thereby obtaining a shape memory polymer composite wire material;

[0091] According to the shape parameters of the required bone repair scaffold, the modeling curve is y using the modeling software NX. 3 =10x 2 , the spacing is 0.6 mm, the curve diameter is 0.8 mm, and the stress-induced structural bone scaffold model is established, such as Figure 1 As shown; after exporting the STL file, it is sliced ​​through the slicing software bambu studio to generate a fused deposition model 3D printing G code, and the shape memory polymer composite filament is placed in a 3D printer for 3D printing. The printing temperature is 220°C, the printing speed is 80mm / s, and the printing layer thickness is 0.2mm to obtain a bionic structure shape memory polymer bone repair scaffold, which is recorded as PWH20 / PEG4.

[0092] Comparative Example 1

[0093] The only difference from Example 1 is that the white phosphate is not annealed, and the white phosphate is compounded with polyethylene glycol and polylactic acid granules. Other conditions are the same as those in Example 1, and a bionic structure shape memory polymer bone repair scaffold is obtained, which is recorded as WH10.

[0094] Comparative Example 2

[0095] The only difference from Example 1 is that no white phosphate piezoelectric particles are added, and only polyethylene glycol is added as a modified material. The content of polyethylene glycol in the polylactic acid-polyethylene glycol composite material is 10%. Other conditions are the same as in Example 1, and a bionic structure shape memory polymer bone repair scaffold is obtained, which is recorded as PEG10.

[0096] The composite material prepared in Comparative Example 2 did not contain white calcium phosphate piezoelectric particles, and the CV curve had no obvious current-voltage change and no electrical activity.

[0097] Comparative Example 3

[0098] The only difference from Example 1 is that polyethylene glycol is not added, and only white calcium phosphate piezoelectric particles are added as modified materials. The content of white calcium phosphate piezoelectric particles in the polylactic acid-white calcium phosphate composite material is 10%. Other conditions are the same as in Example 1, and a bionic structure shape memory polymer bone repair scaffold is obtained, which is recorded as PWH10 / PLA90.

[0099] The composite material prepared in Comparative Example 3 has good electrical activity and a glass transition temperature of above 50° C., which is greater than the temperature that human bone tissue can withstand.

[0100] Comparative Example 4

[0101] The only difference from Example 1 is that the content of the white patite piezoelectric particles in the white patite-polyethylene glycol-polylactic acid composite material is 2.5%, and the other conditions are the same as in Example 1, and a bionic structure shape memory polymer bone repair scaffold is obtained, which is recorded as PWH2.5.

[0102] Figure 1 Model diagram and actual diagram of the stress-induced structural bone scaffold established in Examples 1 to 3 of the present invention, (a) stress-induced model diagram of different spacings and curve diameters in Examples 1 to 3, where l represents the spacing and d represents the curve diameter; (b) actual diagram of the stress-induced structural bone scaffold prepared in Examples 1 to 3, corresponding to Examples 1 to 3 from left to right.

[0103] Figure 2 The XRD pattern of the white calcium phosphate prepared in Example 1 of the present invention; Figure 2 It can be seen that the produced white calcium phosphate has high purity.

[0104] Figure 3 The DSC curves of the shape memory polymer bone repair scaffolds with different contents of white calcium phosphate piezoelectric particles and different contents of polyethylene glycol prepared in Examples 1 to 3 of the present invention and Comparative Examples 2 to 3; Figure 3It can be seen that the glass transition temperature of PWH10 prepared in Example 1 is 41.7°C, which is 20.1°C lower than that of pure polylactic acid material (glass transition temperature is 61.8°C). The glass transition temperature of PWH20 prepared in Example 2 is 42.1°C, which is 19.7°C lower than that of pure polylactic acid material. The glass transition temperature of PWH20 / PEG4 prepared in Example 3 is 45.2°C, which is 16.7°C lower than that of pure polylactic acid material. The glass transition temperature of PEG10 prepared in Comparative Example 2 is 38.6°C, which is 23.2°C lower than that of pure polylactic acid material. The glass transition temperature of PWH10 / PLA90 prepared in Comparative Example 3 is 60.16°C, which has no obvious change in glass transition temperature compared with pure polylactic acid material, and is not within the temperature range adapted to the human body.

[0105] Figure 4 The shape recovery rates of the different white calcium phosphate piezoelectric particles and the shape memory polymer bone repair scaffolds with different polyethylene glycol contents prepared in Examples 1 to 3 and Comparative Examples 1 to 4; Figure 4 As shown, the shape recovery rate of the stress-induced structural bone scaffold prepared in Example 1 is 98.3%, and the shape recovery rate of the stress-induced structural bone scaffold prepared in Example 2 is 96.5%; the shape recovery rate of the stress-induced structural bone scaffold prepared in Example 3 is 95.7%, the shape recovery rate of the stress-induced structural bone scaffold prepared in Comparative Example 1 is 94.6%, which can only meet the shape memory performance requirements, the shape recovery rate of the stress-induced structural bone scaffold prepared in Comparative Example 2 is 99.5%, which can only meet the shape memory performance requirements, the shape recovery rate of the stress-induced structural bone scaffold prepared in Comparative Example 3 is 97.5%, and the shape recovery rate of the stress-induced structural bone scaffold prepared in Comparative Example 4 is 98.7%, which meets the shape memory performance requirements.

[0106] Figure 5 The CV curves of the electroactivity of the shape memory polymer bone repair scaffolds with different white calcium phosphate piezoelectric particles and polyethylene glycol content prepared in Examples 1 to 2 and Comparative Examples 1 and 4, PWH10 corresponds to Example 1, PWH20 corresponds to Example 2, WH10 corresponds to Comparative Example 1, and PWH2.5 corresponds to Comparative Example 4. Figure 5 As shown, the CV curves prepared in Examples 1 to 2 have obvious current-voltage changes and are electrically active, while the CV curve of the material in Comparative Example 1 has no obvious current-voltage changes and is electrically inactive; the composite material prepared in Comparative Example 4 has poor electrical activity.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a white phosphate-polyethylene glycol-polylactic acid shape memory polymer, comprising the following steps: Calcium hydroxide, magnesium hydroxide, water and phosphoric acid are mixed, heated for reaction, aged and dried to obtain white phosphate calcium stone; annealing the whiojasite to obtain whiojasite piezoelectric particles; Compounding polylactic acid, polyethylene glycol, a dissolving agent and white patrolite piezoelectric particles, and drying to obtain a white patrolite-polyethylene glycol-polylactic acid composite material; Extruding the calcium phosphate-polyethylene glycol-polylactic acid composite material to obtain a shape memory polymer composite wire; The shape memory polymer composite filament is 3D printed to obtain the white phosphate-polyethylene glycol-polylactic acid shape memory polymer.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the calcium hydroxide, magnesium hydroxide and phosphoric acid is 0.37-0.38:0.12-0.13:0.4-0.

6.

3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the heating reaction is 90-100° C., and the time is 8-12 hours; the temperature of the aging is room temperature, and the time is 10-16 hours.

4. The preparation method according to claim 1, characterized in that: The annealing treatment is carried out at a temperature of 600 to 750° C. and for a time of 2 to 4 hours.

5. The preparation method according to claim 1, characterized in that: The content of the white patite piezoelectric particles in the white patite-polyethylene glycol-polylactic acid composite material is 10-30wt%; the content of the polyethylene glycol in the white patite-polyethylene glycol-polylactic acid composite material is 3-15wt%; the content of the polylactic acid in the white patite-polyethylene glycol-polylactic acid composite material is 60-86wt%.

6. The preparation method according to claim 1 or 5, characterized in that: The solvent includes dichloromethane, chloroform or ethyl acetate; the ratio of the mass of the solvent to the total mass of polyethylene glycol and polylactic acid is 1:4 to 1:

7.

7. The preparation method according to claim 1, characterized in that: The 3D printing conditions include: a printing temperature of 190 to 230° C., a printing speed of 50 to 100 mm / s, and a printing layer thickness of 0.1 to 0.3 mm.

8. The preparation method according to claim 1, characterized in that: The temperatures of the two extrusion stages are 150-185°C and 140-170°C.

9. The white patrite-polyethylene glycol-polylactic acid shape memory polymer prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the white patrolite-polyethylene glycol-polylactic acid shape memory polymer according to claim 9 in preparing a bone repair scaffold, characterized in that: The method of application includes: Using NX modeling software, modeling was performed based on the biological force line distribution and staggered structural characteristics of the human femur to obtain a stress-induced structural bone scaffold model; After exporting the stress-induced structural bone scaffold model to an STL file, slicing is performed using slicing software to generate a fused deposition model 3D printing G code, and the shape memory polymer composite wire material according to claim 1 is 3D printed to obtain a bionic structure shape memory polymer bone repair scaffold; The modeling curve of the stress-induced structural bone scaffold is y 3 =10x 2 , the spacing is 0.4~0.8mm, and the curve diameter is 0.4~0.8mm.

Citation Information

Patent Citations

  • A preparation method of a 3D printed bionic mandibular scaffold based on TPMS design

    CN113768666B

  • Piezoelectric polyaryletherketone bone repair scaffold as well as preparation method and application thereof

    CN118949128A

Cited By

  • Intelligent degradable three-dimensional porous scaffold with piezoelectric activity as well as preparation method and application of intelligent degradable three-dimensional porous scaffold

    CN120939284A